How does Malaysian use electronic cigarette? A descriptive analysis of the patterns - Ab Rahman, Norny Syafinaz; Nik Mohamed, Mohamad Haniki; Ab Rahman, Jamalludin; Kartiwi, Mira; Draman, Samsul (Wolters Kluwer Health, 2020)
Introduction: Electronic cigarette is gaining its popularity among Malaysians. Thus, there is a need to assess patterns of electronic cigarette use among Malaysian adults. Objectives: To investigate patterns of electronic cigarette use among adults in Malaysia. Cost, side effects, quit attempt and withdrawal symptoms of electronic cigarette use were also examined. Materials and methods: Data were analysed from the National E-Cigarette Survey (NECS) 2016 which used a multi-stage stratified cluster sampling household survey representing all Malaysian adults aged 18 years at national and urban/rural levels. A total of 4,288 adults from all the states were involved in the study. Results: Mean age started to smoke electronic cigarette daily at 26.7 years and the main reason was to